THE EFFECT OF RISK MANAGEMENT IMPLEMENTATION ON RETURN ON ASSETS OF INDONESIAN CONVENTIONAL COMMERCIAL BANKS AFTER THE COVID 19 PANDEMIC IN THE DIGITAL ECONOMY ERA - Rahayu, Sri; Soetjipto, Ken Sabardiman; Sutarman; Arifin, Ahmad; Zen, Ahmad Bachtiar (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Banks are essential for economic stability and growth. Capital adequacy and profitability of banks determine their stability. As one of the profitability metrics, Return on Assets (ROA) is positively correlated with financial performance and negatively correlated with risk-taking; therefore, the implementation of risk management greatly influences bank profitability and is considered important. In the era of the digital economy, accelerated by the COVID-19 pandemic, banks have embraced digital transformation in risk management practices, potentially altering traditional metrics' impact on profitability. This study uses a quantitative analysis approach, analyzing data from banking companies listed on the Indonesia Stock Exchange (IDX) during 2021-2022 through regression models to investigate the impact of risk management on ROA of conventional commercial banks in Indonesia after the COVID-19 pandemic in the digital economy era. The results showed that NIM has a positive influence and significant value on ROA of ordinary commercial banks. LDR has a negative and insignificant impact on ROA of conventional commercial banks, while BOPO has a positive and significant impact. The findings underscore the nuanced roles of NIM, LDR, and BOPO in shaping ROA in the digital economy era, offering insights for bank managers and policymakers to refine risk management strategies in Indonesia's evolving banking landscape